Analysis of a DNA computing readout method based on real-time PCR with taqman probes - Ibrahim, Zuwairie (2007)
In the previous paper, a novel readout approach forthe Hamiltonian Path Problem (HPP) in DNAcomputing based on the real-time polymerase chainreaction (PCR) is proposed. Based on this approach,real-time amplification was performed with theTaqMan probes and the TaqMan detection mechanismwas exploited for the design and development of theproposed readout approach. The readout approachconsists of two steps: real-time amplification in vitrousing TaqMan-based real-time PCR, followed byinformation processing in silico to assess the results ofreal-time amplification, which in turn, enablesextraction of the Hamiltonian path. In this paper, theanalysis of the readout approach is presented, whichconsists of the comparison of the experimental resultwith that of conventional graduated PCR approach.Furthermore, the behavior of TaqMan-based real-timePCR is experimentally investigated in terms of theinitial concentration of template and TaqMan probes.